Witch-children from Salem witch-hunts to modern courtrooms - Sebald, Hans (Prometheus Books, 1995)
The period of persecution and execution of so-called witches stands as a venomous chapter of Western civilization. The hunt extended from the Middle Ages into the early modern era and from the Old World to the New. Although efforts have been made to understand this mass murder, many disturbing aspects remain shrouded in mystery. Witch-Children exposes one of the darkest corners of this time of fear and hysteria that gripped civilized society. The participation of small children and adolescents, whether as the accused or as the accusers, was pivotal. It linked the power of the inquisitor to the fates of many unsuspecting men and women - people who often became hapless victims, devoured by a ravenous inquisition that stretched across two continents. Dr. Hans Sebald examines this sinister nexus by looking at a number of historic witch trials, including those of Salem (Massachusetts), England, Sweden, Austria, and the German territories